FAKTOR – FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN MODAL INTELEKTUAL (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun 2012 - 2013) - Andika, Yusfendy Tri; Laksito, Herry (Diponegoro Journal of Accounting, 2015)
The main objective of this study was to examine factors - factors that affect the disclosure of intellectual capital in the banking companies listed in Indonesia Stock Exchange in 2012 - 2013. The variables used are the Intellectual Capital Disclosure Item, Age Bank, Bank Size, Leverage, Ownership Concentration, profitability, growth, and the type of Auditors. Measurement of intellectual capital items using models of Bukh et al. 2005, namely employees, customers, information technology, processes, and reporting strategies.The sample used is secondary data from the Indonesia Stock Exchange (IDX) ie Annual Report banking company in 2012 listing on the Stock Exchange. Samples were taken by purposive sampling method, and who meet the criteria for sample selection. The sample used by 27 banks from a total of 39 banks are used.The method is applied using multiple regression analysis, the statistical test of hypothesis testing and statistical test t F. The results showed that the age of the bank, the size, and the concentration of ownership has a significant influence on the intellectual capital pengunkapan. However, this study did not find a positive effect on leverage, profitability, growth, and types of auditors on the disclosure of intellectual capital.